The Advantages Of Nuclear Energy Over Other Energy Sources - D.I. Abdusamadova; R.M. Eshburiyev; M. Fayzullaeva; D. Sharipov (Zien Journals, 2025)
This article provides information on the advantages of nuclear energy over other energy sources and its economic efficiency. It discusses the energy released during the fission of uranium and thorium isotopes in nuclear reactors, the formation of these isotopes, the operating principles of nuclear reactors, the use of uranium and plutonium as fuel, the processes of producing these isotopes, and the difference and superiority of the energy released from the fission of uranium-235 nuclei compared to energy obtained via chemical means. Furthermore, the equivalence of energy released in nuclear reactions and in thermonuclear fusion reactions is also addressed. Some research on the safety issues of nuclear energy is included. In addition, the prospects for nuclear energy in Uzbekistan are discussed, along with relevant safety issues.
Keywords: nuclear energy; nuclear reactor; chain reaction